Решить уравнения 1)x^4-(a^2+9)x^2+9a^2=0 2)x^4-(9a^2+4)x^2+36a^2=0 3)(x-1)^4-x^2+2x-73=0 4)(x+2)^4+2x^2+8x-16=0

Решить уравнения 1)x^4-(a^2+9)x^2+9a^2=0 2)x^4-(9a^2+4)x^2+36a^2=0 3)(x-1)^4-x^2+2x-73=0 4)(x+2)^4+2x^2+8x-16=0
Гость
Ответ(ы) на вопрос:
Гость
1)x^4-(a^2+9)x^2+9a^2=0 y=x² y²-(a²+9)y+9a²=0 D=(a²+9)²-4*9a²=a⁴+18a²+91-36a²=a⁴-18a²+91=(a²-9)² y₁=(a²+9-(a²-9))/2=18/2=9      x₁=3   x₂=-3 y₂=(a²+9+(a²-9))/2=2a²/2=a²   x₃=a   x₄=-a 2)x^4-(9a^2+4)x^2+36a^2=0 y=x² y²-(9a²+4)y+36a²=0 D=(9a²+4)²-4*36a²=81a⁴+72a²+16-144a²=81a⁴-72a²+16=(9a²-4)² y₁=(9a²+4-(9a²-4))/2=8/2=4  x₁=2   x₂=-2 y₂=(9a²+4+9a²-4)/2=9a²       x₃=-3a  x₄=3a 3)(x-1)^4-x^2+2x-73=0 (x-1)⁴-(x²-2x+1)-72=0 (X-1)⁴-(x-1)²-72=0 y=(x-1)² y²-y-72=0 D=1-4*72=289=17² y₁=(1-17)/2=-8 y₂=(1+17)/2=9 (x-1)²=-8 нет решений (x-1)²=9 x-1=3   x-1=-3 x₁=4     x₂=-2 4)(x+2)^4+2x^2+8x-16=0 (x+2)⁴+2(x²+4x+4)-8-16=0 (x+2)⁴+2(x+2)²-24=0 (x+2)²=y y²+2y-24=0 D=2²+4*24=100 y₁=(-2+10)/2=4 y₂=(-2-10)/2=-6 (x+2)²=-6 нет решений (x+2)²=4 x+2=2 x₁=0 x+2=-2 x₂=-4
Не нашли ответ?
Ответить на вопрос
Похожие вопросы